Characterization of Physical and Motor Disability at the Technical University of ManabÃ and Its Relationship with Resilience - MacÃƒÂas, Tania Maritza DÃƒÂaz; Meza, Anicia Katherine Tarazona; Garcia, Bibian Bibeca Bumbila; Bozada, Madeleine Alexandra TÃƒÂ³ala (International Research Journal of Management, IT & Social Sciences, 2018)
The work aims to determine the characterization of physical and motor disability and its relation to resilience in the students of the Technical University of ManabÃ. The paper shows an analysis of physical motor disability in students and its impact on the level of resilience. The resilience analysis was addressed terms physical and mental state of the people, as well as the process of adapting to the problems and adversities of life. The results were shown in tables and graph on the analysis of the degree of physical-motor disability of the students as well as the application of the SV-RES test prepared by the researchers Saavedra & Villalta, 2008. Based on the evaluation of 12 dimensions, which they allow to verify the situation according to three scales: high, average and low. Finally, the conclusions were offered where the objective stated in the investigation was verified.